The Effects of Problem Based Learning (PBL) assisted by the Powtoon Application to Improve Students' Learning Outcomes - Armiati, Armiati; Nurhafizah, Nurhafizah; Hidayat, M Topit; Rahmidani, Rose (JETL (Journal of Education, Teaching and Learning), 2024)
Teachers play an important role in using appropriate learning strategies, so that they can improve student learning outcomes. This research aims to find out differences in economic learning outcomes using learning models problem based learning media assisted Powtoon with conventional learning for class XI students at SMA Pertiwi 1 Padang. This type of research is research quasi experimental design. The research population consisted of all 244 students in class Data collection techniques using observation, tests and documentation. Data analysis techniques use normality tests, homogeneity tests and hypothesis tests. The research results show mark posttest learning model problem based learning media assisted powtoon of 80.11 and value posttest conventional learning is 68.11 with a difference of 12. And also learning models problem based learning media assisted powtoon influence on student learning outcomes. It was concluded that there were differences in student learning outcomes who used the learning model problem based learning media assisted powtoon with conventional learning